Broadband controllable acoustic focusing and asymmetric focusing by acoustic metamaterials. (12th March 2021) - Liao, Guangxin; Wang, Zhenwei; Luan, Congcong; Liu, Jiapeng; Yao, Xinhua; Fu, Jianzhong
Abstract: The applications of acoustic focusing and acoustic asymmetric focusing (AAF) are severely constrained by the narrow frequency bandwidth. In this paper, we report broad bandwidth acoustic focusing lens and asymmetric acoustic focusing lens consisting of monolayer and dual-layer metamaterials, respectively. Additive manufacturing technology was utilized to fabricate the designed lens. Finite element analysis and experimental approaches are adopted to verify the performances of acoustic focusing and asymmetric acoustic focusing. The results demonstrate that the designed acoustic focusing lens can converge acoustic waves at the frequency from 4717 Hz to 7717 Hz. The excellent AAF effect can be realized at a large frequency range from 4717 Hz to 6717 Hz. The results of measurement are consistent well with the simulated ones. Besides, by changing the separation between the dual-layer metamaterials for the AAF lens, the focusing position can be controlled without changing the metamaterials structure. Our approach may offer an efficient method to design broadband acoustic focusing and AAF devices and promote the important applications in numerous practical fields, including acoustic absorption and noise reducing, acoustic energy harvesting, ultrasonic medicine and multifunctional materials.